H1N1 disseminated infection in a 3-month-old boy - Moniz, M (2019)
Earlier this year a new influenza virus emerged. In children, the clinical manifestations of H1N1 infection are similar to those reported during periods of seasonal influenza. We report on a 3-month-old boy with an upper respiratory tract infection who presented enteropathy, coagulopathy and encephalitis related to H1N1. The infection was confirmed in nasopharyngeal aspirate, stools and cerebrospinal fluid by real-time PCR. Treatment with oseltamivir was started.